KNOWLEDGE SHARING IN SMALL AND MEDIUM SCALE ENTERPRISES IN BENIN CITY, EDO STATE - Omogeafe Ohiorenoya, John; Obadan, Joseph Avunun (European Scientific Journal, ESJ, 2014)
The paper compared knowledge sharing in two companies in the hospitality business. Three aspects of knowledge sharing; knowledge internalization, knowledge sharing method, and barriers to knowledge sharing were examined. Two firms were compared and contrasted on the basis of these four aspects of knowledge sharing. The paper adopted stratified sampling technique and divided employees into top management, middle management, supervisory management and others. Questionnaires were used, supplemented by personal observation. A sample of 67 employees was used for the study. The method of analysis was descriptive statistics using mean as the basis for our findings. Findings were: differences and similarities existed between the two companies with respect to knowledge internalization, preferred method of knowledge sharing, knowledge infrastructure and barriers to knowledge sharing. The paper recommended discovery and innovation as a panacea for removing barriers to knowledge sharing and paying attention to employing more educated and experienced people to improve knowledge sharing.